Efficacy and safety of anlotinib for the treatment of advanced bone and soft tissue sarcomas: a systematic review and meta-analysis - Li, Zhipeng; Fang, Peng; Shen, Shiwen; Zhang, Lei; Xie, Rui; Li, Chengjun (Frontiers in Oncology, 2025)
BackgroundSarcoma, a rare and highly heterogeneous malignant neoplasm originating from mesenchymal tissues, is broadly classified into bone sarcoma and soft tissue sarcoma depending on where they occur. Patients with advanced or metastatic sarcomas face a poor prognosis. Conventional chemotherapy regimens demonstrate limited efficacy with substantial adverse effects, and therapeutic options remain scarce for those experiencing chemotherapy failure or intolerance. The development of tyrosine kinase inhibitors has brought the treatment of sarcoma into a new stage. As a multi-target tyrosine kinase inhibitor, anlotinib exerts antitumor effects through dual mechanisms of anti-angiogenesis and direct tumor cell proliferation inhibition. While it has been increasingly reported to treat bone and soft tissue sarcoma with promising efficacy, there has been no systematic analysis of this application.MethodsPubMed, Embase, the Cochrane Library, Web of Science, Vip (China), Cnki (China), WanFang (China), and SinoMed (China) databases were systematically searched for relevant studies, published from the inception of each database to July 12, 2025, without language restrictions. The primary outcomes included the objective response rate (ORR), disease control rate (DCR), progression-free survival (PFS), overall survival (OS), and adverse events (AEs). These data were extracted and analyzed using STATA 17.0 software.ResultsA total of 16 studies with 787 participants were included in this meta-analysis. In terms of clinical efficacy, the pooled outcomes indicated that ORR and DCR were 8.8% (95%CI: 6.2%–11.7%) and 70.7% (95%CI: 64.8%–76.2%), respectively. Median PFS ranged from 2.7 to 12.4 months, with a pooled result of 6.68 months (95%CI: 5.37–7.98). Median OS ranged from 11.4 to 42 months, with a mean of 19 ± 9.5 months. Furthermore, the 3-, 6-, and 9-month PFS rates were 71.1%, 48.4%, and 32.0%, respectively. The 6- and 12-month OS rates were 85.7% and 67.8%, respectively. With regard to clinical safety, the three most common all-grade treatment-related adverse events associated with anlotinib were hand-foot syndrome (34.7%), hypertension (32.4%), and pharyngalgia (30.6%). However, the incidence of grade 3–4 adverse events was relatively low and manageable; for example, hypertension (7.9%), hand-foot syndrome (2.9%), and pneumothorax (3.0%).ConclusionsBased on the evidence provided by this meta-analysis, anlotinib demonstrates promising clinical efficacy and a favorable safety profile in patients with advanced bone and soft tissue sarcomas, although additional high-quality clinical studies are required to further evaluate its properties and toxicity.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251103981, PROSPERO.